SYNCHRONIZATION OF SOCIAL BOND ISSUANCE SETTINGS AS A FINANCING INSTRUMENT FOR AFFORDABLE HOUSING IN INDONESIA - Firzatul Rima Fitriana; Budi Endarto (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This article examines the legal synchronization of social bond issuance as an alternative financing instrument for the fulfillment of affordable housing needs in Indonesia. The central issue of this study is the lack of alignment between social bond regulations and affordable housing provisions, which hinders the achievement of sustainable urban development. The objective of this research is to formulate a juridical basis capable of harmonizing social bond requirements with affordable housing targets. This study employs normative legal research through statutory and conceptual approaches. The results indicate that the provisions of POJK 18/2023 on social bonds are not yet aligned with affordable housing regulations contained in Government Regulation 12/2021, Government Regulation 21/2024, and Regulation of the Minister of Public Works and Housing 7/2022, creating obstacles to effective implementation. A horizontal synchronization model is required to harmonize these regulatory frameworks, particularly to support economic equalization under the Asta Cita Program designated as a National Priority in the National Medium-Term Development Plan 2025–2029. The study concludes that regulatory synchronization is essential to ensure the effectiveness of social bonds as a financing instrument for affordable housing in Indonesia.